Realisasi Electronic Government melalui Layanan Pengaduan Medan Rumah Kita di Kota Medan - Sri Maya Paradissa; Februati Trimurni (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
This study aims to describe and examine the realization of the successful elements of electronic government development through the Medan Rumah Kita Complaint Service in Medan City. This research uses a descriptive method with a qualitative approach. Data collection was carried out using structured observation, documentation, literature study, and in-depth interviews through purposive and snowball sampling. The results of the study show that government support is well realized through the power of regulations governing the Medan Rumah Kita Complaint Service from the center to the regions. It's just that a clear guarantee of time is needed in completing complaints. Then, on the capacity indicator, the government is able to provide adequate financial, infrastructure and human resources. It's just that the Medan Rumah Kita Complaint Service has not been integrated with other services and the features displayed must be presented more fully so that people are comfortable using them. Then, on the value indicator, the public can freely interact with the government without having to go to the relevant agency and wait a long time, even though there are still some unresponsive services. Thus, various obstacles to the Medan Rumah Kita Complaint Service must be addressed in order to realize Medan City as a Smart City.